Delivery of gene therapy to resting immune cells for an HIV cure. Issue 2 (March 2019) - Ahlenstiel, Chantelle L.; Turville, Stuart G.
Abstract : Purpose of review: The utilization of genetically modified T cells to therapeutically target to various previously incurable diseases such, as cancer, has expanded exponentially in recent years. This success now provides the motivating force in applying the same technology for incurable infectious diseases including HIV. The common bottleneck in gene therapy continues to be at the level of gene delivery. Although present approaches adapt the cell to the delivery technology, emerging techniques now focus on leaving cells in their phenotypically resting state. In doing so, engraftment and proliferation potential are retained and in turn increase the efficacy of this approach at a lowered cost. This review will outline the main efforts of gene delivery using viral vectors or nonviral vectors and challenges moving forward not only in resting T cells, but also in other resting immune cells including hematopoietic stem cells. Recent findings: In focusing on HIV cure efforts using gene therapy, progress on solving the challenges of gene delivery will be described for both viral and nonviral vectors. Advances in the basic virology of lentiviruses have led to the proposal of many next generation lentiviral vector platforms for resting immune cells. Moreover, we will also highlight the progress made in nonviral approaches using nanotechnology as alternatives and/or synergistic technologies to be used alongside lentiviral platforms. Summary: The innovative approaches described in these recent studies, particularly those using the natural mechanisms employed by HIV to enhance for example virus entry or virus latency, will enable future optimization of gene delivery platforms and therapeutics, which will importantly, provide a pathway toward translation into clinical practice.